Kajian Pengembangan Industri Pangan Kreatif Berbahan Baku Kelapa Di Kabupaten Minahasa Selatan - Koapaha, Teltje; Pinatik, Herry F.; Langi, Tineke M.; Tooy, Dedie (Jurnal Teknologi Pertanian (Agricultural Technology Journal, 2018)
Agricultural development over the past decade, is more identical tocommodity development, which focuses on meeting domestic food needs.The development of globalization, a country in this case the government,must be able to facilitate and encourage the community to developproductive activities, including developing the creative food industry,which is characterized not only by fulfilling quantity, quality, but havingselling value, or the value of excellence product specifics (prepositionvalue), and provide economic (added value). The synergy of various parties(stake holders) encourages increased production of creative food productsby intensifying : technology, information, ideas and creativity as well asskills that emerge from the community, both individual farmers andindustrial groups in the South Minahasa Regency.The objectives of this study are: 1. Identify the types and characteristicsof coconut-based food industries in South Minahasa regency and 2.Calculate the economic added value of the development of coconut-basedfood industries in South Minahasa regency. 3. Obtain appropriate methods,strategies and models for the development of a food industry based oncoconut in South Minahasa Regency. This study uses several methods,namely: descriptive method, calculation of added value according to Costerand Schaffer, 1982) and the SWOT method for obtaining methods,strategies and models for the development of creative food industries thatare suitable in South Minahasa regency. The results showed that there were3 types of development of creative food industries made from coconutwhich already existed in South Minahasa Regency, namely: 1. culinary, 2.medicines 4. research development. From this type of creative foodindustry, it has provided real economic added value for farmers, industrialgroups and macro for the economic growth of the community, whenapplying methods, strategies and models that match the potential andcharacteristics in South Minahasa Regency.Keywords: development, creative food industry, coconut raw materials